Determinants of Vietnam’s outward direct investment: The case of Cambodia - Võ, Thanh Thu (University of Economics Ho Chi Minh City, 2023)
This research focuses on the determinants of Vietnam’s outward FDI by studying simultaneously the influence of two pull factors and push factors. In addition, the work examines the differences in assessing the impact of two factors groups on investment decisions by market entry method. The authors conduct qualitative research interviewing six experts as the managers have an important role in the decision to invest directly abroad for their business and quantitative research by multiple regression methods studying samples consisting of 248 enterprises. Push factors group from Vietnam includes competitive pressure of Vietnam market, monetary policy, interest rates of Vietnam, regulations and procedures for licensing investment abroad of Vietnam, incentive policy, and investment incentives to overseas. Pull factors group from host country includes culture–geography, macroeconomics and market, infrastructure, regulations and policies related to investment. Through two groups of factors, the authors withdraw into four groups that impact the Vietnam’s FDI abroad including: (i) culture–geography, (ii) infrastructure; (iii) the macro-economic and market; and (iv) regulations and policies related to investment. The results indicate that two groups of factors, both pull factors and push factors, have impact on Vietnam’s FDI abroad.